2021
DOI: 10.7717/peerj.10656
|View full text |Cite
|
Sign up to set email alerts
|

High expression of MAPK-14 promoting the death of chondrocytes is an important signal of osteoarthritis process

Abstract: Background Osteoarthritis (OA) is one of the most common degenerative diseases worldwide. Many researchers are studying the pathogenesis of OA, however, it is still unclear. Methods Screening and validation of OA relevant hub genes are an important part of exploring their potential molecular mechanism. Therefore, this study aims to explore and verify the mechanisms of hub genes in the OA by bioinformatics, qPCR, fluorescence and propidium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…We recently confirmed that increased expression of COL I, decreased expression of COL II, a disordered cytoskeletal protein distribution, and loss of cell membrane integrity are important characteristics of OA, indicative of a decrease of anabolism of human OA chondrocytes [ 7 ]. We also confirmed that high expression of MAPK-14 may promote chondrocyte death [ 8 ]. Another study found that among several important proteoglycan proteases involved in matrix catabolism, the expression levels of MMP and aggrecanases (ADAMTs) are significantly higher in OA synovial fluid and joint tissues.…”
Section: Introduction and Epidemiologysupporting
confidence: 77%
“…We recently confirmed that increased expression of COL I, decreased expression of COL II, a disordered cytoskeletal protein distribution, and loss of cell membrane integrity are important characteristics of OA, indicative of a decrease of anabolism of human OA chondrocytes [ 7 ]. We also confirmed that high expression of MAPK-14 may promote chondrocyte death [ 8 ]. Another study found that among several important proteoglycan proteases involved in matrix catabolism, the expression levels of MMP and aggrecanases (ADAMTs) are significantly higher in OA synovial fluid and joint tissues.…”
Section: Introduction and Epidemiologysupporting
confidence: 77%
“…Makino that has many pharmacological functions, such as anti-inflammatory ( Lin et al, 2020 ; Wang et al, 2021b ), anti-tumor ( Han et al, 2011 ; He et al, 2013a ; He et al, 2013b ; He et al, 2014 ; Kang et al, 2016 ), anti-fungal, anti-cough, and analgesic activities. The MAPK, together with NF-κB signaling pathway, is thought to play crucial roles in the development of OA, as activation of these two pathway causes cartilage inflammation and damage ( Lianxu et al, 2006 ; Lepetsos et al, 2019 ; Chuntakaruk et al, 2021 ; Deng et al, 2021 ). Therefore, inhibition of these pathways may be a method of OA treatment ( Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such inflammatory factors can combine with receptors on the articular cartilage surface to activate the NF-κB, p38 MAPK, JNK, and ERK1/2 pathways in chondrocytes. They can also induce MMPs production for proteoglycan and collagen degradation in cartilage ( 33 - 35 ). The NF-κB pathway accounts for an important regulating factor for chondrocyte inflammation ( 36 , 37 ), and its activation plays a key role in producing inflammatory factors like iNOS and COX-2 ( 38 ).…”
Section: Discussionmentioning
confidence: 99%